2014
DOI: 10.4238/2014.december.18.11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and expression analysis of somatic embryogenesis receptor-like kinase genes from Phalaenopsis

Abstract: ABSTRACT. Somatic embryogenesis receptor-like kinase (SERK) genes have been found to be involved in the somatic embryogenesis of several plant species. We identified and characterized 5 PhSERK genes in the Phalaenopsis orchid. The amino acid sequences of PhSERKs and other SERK proteins are highly conserved, with the highest homology observed in the leucine-rich repeat-receptor-like kinase domain. All 5 PhSERKs were expressed in all Phalaenopsis organs examined (root, leaf, shoot apical meristem, and flower), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Evaluation of CcSERK1 gene expression demonstrated basal transcription levels in almost every organ of the plant, but the highest ratio was detected in the shoot apical meristem. A similar result was obtained in the Phalaenopsis orchid , where expression of the SERK1 homolog is higher in shoot apical meristem than in any other tissue (Huang et al ). With respect to zygotic embryogenesis, the amount of CcSERK1 transcript increased twice during flower development; the first increase occurred 1 day after anthesis, and the second increase in CcSERK1 transcription occurred just after pollination, which occurs between days four and six after anthesis in coffee flowers (León ).…”
Section: Discussionsupporting
confidence: 75%
“…Evaluation of CcSERK1 gene expression demonstrated basal transcription levels in almost every organ of the plant, but the highest ratio was detected in the shoot apical meristem. A similar result was obtained in the Phalaenopsis orchid , where expression of the SERK1 homolog is higher in shoot apical meristem than in any other tissue (Huang et al ). With respect to zygotic embryogenesis, the amount of CcSERK1 transcript increased twice during flower development; the first increase occurred 1 day after anthesis, and the second increase in CcSERK1 transcription occurred just after pollination, which occurs between days four and six after anthesis in coffee flowers (León ).…”
Section: Discussionsupporting
confidence: 75%
“…Three previously reported SERK-like genes, PaSERK1, PaSERK2, and PaSERK5 (Huang et al, 2014), also were present in our transcriptome database. However, the expression of PaSERK1, PaSERK2, and PaSERK5 was ubiquitous across the tissues we analyzed and did not display embryo-specific patterns ( Table I).…”
Section: Embryo-specific Markers Are Not Enriched In Protocorm and Plmentioning
confidence: 89%
“…Ref. [52] characterized and analyzed the expression of 5 of these genes in Phalaenopsis and which were described by the authors as PhSERK. According to this study, the expression of these 5 genes was observed in various parts of plants (root, leaf, apical bud, and flower meristem) as well as during seed germination and PLB induction.…”
Section: Genus Phalaenopsis and Relatedmentioning
confidence: 99%
“…Although cytological features indicate that a PLB is a somatic embryo and studies have shown PhSERK gene expression during PLB induction [52], transcriptome studies developed by [29] analyzing gene expression in Phalaenopsis aphrodite concluded that PLBs are molecularly distinct from zygotic embryos. According to the authors, PLBs share different transcriptomic signatures from zygotic embryos, and early processes of PLB development show a distinct regeneration program, not following the embryogenesis program.…”
Section: Genus Phalaenopsis and Relatedmentioning
confidence: 99%